Reduced Red Blood Cell Membrane Essential Polyunsaturated Fatty Acids in First Episode Schizophrenia at Neuroleptic-Naive Baseline - Reddy, Ravinder D.; Keshavan, Matcheri S.; Yao, Jeffrey K. (Schizophrenia bulletin, 2004)
There is emerging evidence in schizophrenia of membrane abnormalities, primarily reductions in the essential omega-3 and omega-6 series of polyunsaturated fatty acids (PUFA). Because previous studies have largely been in chronic patients, it is not known whether these membrane abnormalities also occur early in illness. In the present study, red blood cell membrane fatty acid levels were determined by capillary gas chromatography from 24 neuroleptic-naive patients with first episode schizophrenia or schizoaffective disorder and 31 age-matched normal controls. Relative to normal subjects, patients had significant reductions in total PUFA (−13%) but not in monounsaturated or saturated fatty acids. Specifically, significant reductions were found in arachidonic acid (−18%), docosapentaenoic acid (−36%), and docosahexaenoic acid (−26%) concentrations. These reductions were not related to age, gender, smoking status, or cotinine levels. These results confirm previous findings of membrane deficits in schizophrenia and show that significant PUFA reductions occur early in the illness, prior to initiation of treatment, raising the possibility that these deficits are trait related. The findings also suggest that membrane fatty acid losses are quite specific to the highly unsaturated fatty acids.